Study on Reactance Relays for Single Phase to Earth Fault on EHV Transmission Lines - Yongqing Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Two questions about zero-sequence-reactance relay to overcome the disadvantages of high fault resistance for single phase to earth fault of high voltage transmission lines are discussed in this paper. The first question is about the phase difference between the measured zero-sequence current and voltage at fault position for un-balanced transmission lines. The second question is about the “in-phase” problem in reactance relays (or fault component reactance relays). This paper analyzes the two questions theoretically and the reactance relay is improved by a new discriminative principle. The capability against the fault resistance is largely enhanced by the improved schemes. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2835